An In planta-expressed polyketide synthase produces (R)-mellein in the wheat pathogen Parastagonospora nodorum - Chooi, Y.; Krill, C.; Barrow, R.; Chen, S.; Trengove, R.; Oliver, Richard; Solomon, P. (American Society for Microbiology, 2015)
Parastagonospora nodorum is a pathogen of wheat that affects yields globally. Previous transcriptional analysis identified a partially reducing polyketide synthase (PR-PKS) gene, SNOG_00477 (SN477), in P. nodorum that is highly upregulated during infection of wheat leaves. Disruption of the corresponding SN477 gene resulted in the loss of production of two compounds, which we identified as (R)-mellein and (R)-O-methylmellein. Using a Saccharomyces cerevisiae yeast heterologous expression system, we successfully demonstrated that SN477 is the only enzyme required for the production of (R)-mellein. This is the first identification of a fungal PKS that is responsible for the synthesis of (R)-mellein. The P. nodorum ΔSN477 mutant did not show any significant difference from the wild-type strain in its virulence against wheat. However, (R)-mellein at 200 μg/ml inhibited the germination of wheat (Triticum aestivum) and barrel medic (Medicago truncatula) seeds. Comparative sequence analysis identified the presence of mellein synthase (MLNS) homologues in several Dothideomycetes and two sodariomycete genera. Phylogenetic analysis suggests that the MLNSs in fungi and bacteria evolved convergently from fungal and bacterial 6-methylsalicylic acid synthases.